Sulfatide mediates attachment of Pseudomonas aeruginosa to human pharyngeal epithelial cells - (:unkn) unknown (EDIZIONI INT SRL, 2007)
Pseudomonas aeruginosa infections are particularly common in people with cystic fibrosis and despite regular treatment with antibiotics, lung damage due to chronic infection with P. aeruginosa remains the major cause of death in those patients. In order to initiate an infection, R aeruginosa needs contact with the respiratory epithelial surface and by means of its adhesins i.e., fimbria, hemagglutinins,etc., it recognizes and adheres to the corresponding epithelial receptors. We treated R aeruginosa strains isolated from sputum of cystic fibrosis patients with several glycolipids such as sulfatide, sulfated ganglioside mixture (GM1a, GD1b, GT1b), asialo-GM, and galactocerebrosides to determine their effect on attachment with pharyngeal epithelial cells. Sulfated ganglioside mixture and sulfatide inhibited the attachment of R aeruginosa significantly, whereas asialo-GM1, Gal-Cer and sodium sulfite had no effect on attachment inhibition. This finding suggests that sulfated glycoconjugates found in the extracellular matrix, in mucus and on the surface of epithelial cells of human trachea and lung mediates attachment of R aeruginosa.
Keywords: pseudomonas aeruginosa; attachment; epithelial cells; sulfatide; asialo-GM(1); PILI; BINDING; SURFACE; RECOGNITION; ASIALO-GM1; ADHESION; PROTEIN